(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
Thinking about the future of online education, how it interacts with traditional education and how they interact, is important in the development of the modern education system. Today, the rapid development of technologies, the widespread use of the Internet and the possibilities of digital resources require new approaches in the field of education. Along with traditional forms of education, online education plays a major role in making the educational process more efficient and convenient.